PENGGUNAAN METODE PICTURE AND PICTURE UNTUK MENINGKATKAN KEMAMPUAN LITERASI BACA TULIS PADA SISWA KELAS 1 SEKOLAH DASAR - Suri Husni Nuraeni; Asep Samsudin (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2023)
Competencies that must exist at this time are reliable human resources .namely human resources who have literate abilities ( reading and writing). In addition to literate abilities orations skills ( listening and speaking) are also needded,in which the two skills are an integral part of each other. Connected thas is used in everiday life . In everiday life human resources are competent as one to live life by digging up as much inforamtion as possible ao that they become human resources capable of contributing to personal and national progress because a nation will be said to develop if all human resources have awareness of literacy,because literacy will open doors of knowledge that have never been solved before. In that way literacy is the main key in a science.The purpose of this study was to find out and examine the process of apliyying the picture and picture to the learning of elemntary school students in grade 1.also the obstacles faced by teachers and students in carrying out learning using the picture and picture model.